AN ASSESSMENT OF THE IMPACT OF NATURAL RESOURCE RENT, FINANCIAL DEVELOPMENT AND URBANIZATION ON CARBON DIOXIDE EMISSIONS: THE CASE OF TÜRKİYE AND SOUTH AFRICA - Aziza Hashi KORKMAZ; Ayhan KAPUSUZOGLU; Nildag Basak CEYLAN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2023)
Türkiye and South Africa are the most globalized, urbanized and the most carbonintensive economy in the emerging economies. In this direction, this study examines an assessment of the impact of natural resource rent, financial development, and urbanization on carbon dioxide emissions in South Africa and Türkiye. For the period 1990-2021, we have implemented an AutoRegressive Distributed Latency (ARDL). The ARDL cointegration test result shows the existence of a long-term relationship between the variables. The granger causality test indicates that there is a bi directional relationship between carbon dioxide emissions and natural gas rents, financial development and natural gas rent and urbanization and natural gas rent. In addition to, this VAR Granger Causality/Block Exogeneity Wald Tests shows that there is a link between carbon dioxide emissions and financial development.